Stuffed a history of good food and hard times in Britain - Vogler, Pen‏ (Atlantic Books, 2023)
"The fascinating history of the people, the ideas and the dishes that have fed - and starved - the nation, by the author of the Sunday Times bestselling Scoff. In times of plenty, we stuff ourselves. When the food runs out, we're stuffed too. How have people in the British Isles shared the riches from our fields, dairies, kitchens and seas, as well as those from around the world? And when the cupboard is bare, who steps up to the plate to feed the nation's hungry children, soldiers at war or families in crisis? Stuffed tells the stories of the food and drink at the centre of social upheavals from prehistory to the present: the medieval inns boosted by the plague; the Enclosures that finished off the celebratory roast goose; the Victorian chemist searching for unadulterated mustard; the post-war supermarkets luring customers with strawberries. Drawing on cookbooks, literature and social records, Pen Vogler reveals how these turning points have led to today's extremes of plenty and want: roast beef and food banks; allotment-fresh vegetables and ultra-processed fillers. It is a tale of feast and famine, and of the traditions, the ideas and the laws which have fed - or starved - the nation, but also of the yeasty magic of bread and ale, the thrill of sugary treats, the pies and puddings that punctuate the year, and why the British would give anything - even North America - for a nice cup of tea"--Publisher's description